Comparative analysis of fetomaternal outcome in antenatal women infected with pulmonary and extrapulmonary tuberculosis - Lewis, Preeti Frank; Budhewar, Amita Shankarrao; Bavdekar, Nitin Bhimrao; Gurnani, Deepika; Kumari, Ayushi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Active tuberculosis is a multiorgan disease caused by primary infection or as a re-activation of latent tuberculosis. The studies comparing maternal and fetal outcome in antenatal women with extrapulmonary tuberculosis and pulmonary tuberculosis is scanty therefore, in current study we outline and identify the demographic and clinical characteristics of pulmonary tuberculosis and extrapulmonary tuberculosis and comparing fetal and maternal outcome in pulmonary and extrapulmonary tuberculosis. The maternal complications and fetal complications of pulmonary tuberculosis were analysed compare with extra pulmonary tuberculosis. Methods: This was prospective observational study done in tertiary care centre over a period 1.5 year from January 2019 to June 2020. Institute ethical committee approval was obtained. Pregnant women in the age group of 18-42 years diagnosed with tuberculosis in antenatal period were included in our study for comparing fetal and maternal outcomes. They were evaluated for their symptom including clinical examination, microbiological, radiological and biochemical testing. We excluded those antenatal women with tuberculosis and adequately treated and cured and those women with tuberculosis who did not delivered during study period. Results: Most common complication associated with pulmonary tuberculosis was intrauterine growth restriction whereas in extrapulmonary preterm labour most common complication. Perinatal outcome worse in extrapulmonary tuberculosis as compared to pulmonary tuberculosis. Conclusions: Pregnancy with tuberculosis worsen the outcome of both mother and fetus. Our study depicted perinatal outcome is worse in Extrapulmonary TB than pulmonary TB. Atypical presentation of the Extrapulmonary TB may constitute diagnostic and therapeutic challenges thus a high clinical suspicion is needed.